A multifunctional thermal management paper based on functionalized graphene oxide nanosheets decorated with nanodiamond. (May 2020) - Nan, Bingfei; Wu, Kun; Qu, Zhencai; Xiao, Luqi; Xu, Changan; Shi, Jun; Lu, Mangeng
Abstract: In this study, we developed a multifunctional thermal management nanocomposite paper (NPG) consisting of cationic poly (diallyldimethylammonium chloride) (PDDA)-functionalized graphene oxide (PG) and nanodiamond (ND). Due to the functionalized reduction of graphene oxide (GO) by PDDA as well as electrostatic interactions between the positively charged PG and negatively charged ND, a three-dimensional (3D) hybrid NPG paper constructed by two-dimensional (2D) PG layers and zero-dimensional (0D) ND particles was successfully prepared via a vacuum-assisted self-assembly strategy. The resulting NPG papers were characterized by various techniques including Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) pattern and X-ray photoelectron spectroscopy (XPS). In this analogous 3D "panel-bead" structure, adjacent PG nanosheets and ND particles are bridged through electrostatic interactions, which strengthens the interface connection and reduces phonon scatterings, resulting in an effective phonon transport pathway. Thus, a superior in-plane thermal conductivity of 16.653W m −1 K −1 was obtained at the mass ratio of GO:ND = 3:1 (NPG3), which is about 80 times higher than that of traditional pure polymers. In addition, the peak heat release rate (PHRR) of NPG3 paper was only 99.16 W g −1 at 439.2 °C while that of GO was 438.4 W g −1 at 210.9 °C, indicating that NPG paper possesses excellent flame retardancy. More interestingly, although the NPG3 paper has excellent insulation (electrical resistivity reaches up to 2.647 × 10 11  Ω cm), the ultrafast flame alarm response was found within about 1s after the paper exposed to the flame. This design idea provides an alternative approach for preparing multifunctional thermal management nanocomposites in the future. Graphical abstract: Image 1 Highlights: The NPG paper constructed by PG nanosheet and ND particles were prepared via a vacuum-assisted self-assembly strategy. The NPG paper has superior in-plane thermal conductivity of 16.653W m −1 K −1  at the mass ratio of GO:ND = 3:1. The NPG paper shows excellent flame retardancy, electrical insulation and ultrafast flame alarm response capability. This nanocomposite paper provides an option for the multifunctional development of thermal management materials.